Spring 1998 field report, Jane Clark - Clark, Janeet al (1998)
An annotated list of birds sighted by Jane Clark and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1998. Epson - sheet feed